Review of economic bubbles. Issue 4 (August 2016) - Chang, Victor; Newman, Russell; Walters, Robert John; Wills, Gary Brian
Highlights: We provide review of economic bubbles and identify any correlations between different bubbles. Literature has been consulted on historical and recent bubbles. Theories surrounding speculation, the market for venture capital and technology bubbles have been presented. All the economic bubbles are classified under "uncontrolled risk". A method to detect and analyse full impacts by uncontrolled risk should be used. Future directions for economic bubble research have been discussed. Abstract: This paper investigates the history of economic bubbles and attempts to identify whether there are direct correlations between different bubbles. To support this research, literature has been consulted on historical and recent bubbles, theories surrounding speculation, the market for venture capital, and bubbles in the technology sector. By analysing a range of bubbles, rather than just those in the technology sector, general bubble-principles are also identified. All the economic bubbles are classified under "uncontrolled risk" and a recommended method that can detect and analyse full impacts by uncontrolled risk will be presented, together with future directions to be discussed.